Analisis Stabilitas Lereng Menggunakan Software Geoslope pada Sungai Rongkong (Kabupaten Luwu Utara) - Amir, Mursyid; Musa, Ratna; Mallombassi, Ali (Jurnal Kridatama Sains dan Teknologi, 2024)
The use of embankment reinforcement would be very suitable for use on the slopes of the North Rongkong Luwu Watershed (DAS), generally with embankment strengthening being able to overcome natural flood disasters. The aim of this research is to determine the results of the increase (SF) after using geotextile reinforcement and to find out the comparison of the results of slope stability analysis using manual and geoslope calculations. The method used in this research is a descriptive method, namely research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The method used is to compare calculations carried out manually with formulas, compared with calculations using the geoslope application. The results of the landslide stability reading before using reinforcement with the geoslope application as a whole can still be said to have not exceeded the limit that has been determined to prevent landslides. Meanwhile, after using geotextile reinforcement, it has a value that meets the failure limit specifications. The results of manual calculations and using geoslope have a value that is less more similar in analyzing internal, external stability or landslides on slopes around the Rongkong River.